VARIASI JARGON DALAM SUATU KOMUNITAS WARIA DI SALON RETHAH WILAYAH PONDOK BENDA - Amalia, Amanda Rizky; Tauladan, Antika Suri; Sari, Fani Aulia (Prosiding Seminar Nasional Sasindo, 2021)
Language has an important role in everyday human life in society. Jargon is a kind of language that is only used by certain communities as daily communication among its members. The jargon used by the transgender community is very interesting to understand because the jargon has its own form and meaning in its disclosure and can find out how the variety of jargon-shaped language used by transgenders in hiding their secrets so as not to be known by the public. It is evident that not all users of other languages understand the jargon. In this study, the researchers analyzed the jargon used by the waria community in the salon. This study aims to determine the jargon and describe and understand the meaning of the jargon used by the transgender community in interacting orally. The source of the research data was obtained from the subject, namely the transgender women who worked at the Retah salon in Pamulang, who used jargon in their daily communication with transgender women and sometimes with their customers. The method used in this study is a qualitative descriptive method, which describes and conveys data objectively. Describe the jargon terms of transgender language as the object of research. The data collection technique used is observation or see and note. The result of this research is the jargon used by waria in the form of transgender language vocabulary. Based on the results of the data analysis, it was found that 20 pieces of jargon used by transgender women in the salon were akika, rapose, capcus, endang gurindang, ink, sekong, belenjong, cucok, metong, hamidah, lekong, sapose, capcay, begindang, bala-bala, sindang. , lambreta, grasshopper, mesong, and mursida.Keywords: Waria, Jargon, Vocabulary